3D Assembly: Micro/Nanoscale 3D Assembly by Rolling, Folding, Curving, and Buckling Approaches (Adv. Mater. 36/2019). Issue 36 (3rd September 2019) - Cheng, Xu; Zhang, Yihui
Abstract : In article number 1901895, Yihui Zhang and Xu Cheng discuss the latest progress and new perspectives of micro‐/nanoscale 3D assembly, highlighting the various methods, through rolling, folding, curving, and buckling assembly. Owing to their broad‐ranging applicability to different material systems, the resulting 3D micro‐/nanostructures have compelling applications in widespread areas, from electronics/optoelectronics, and microelectromechanical systems (MEMS), to medical devices and cell scaffolds.